Astrophysical constraints on the simulation hypothesis for this Universe: why it is (nearly) impossible that we live in a simulation - Vazza, F. (Frontiers in Physics, 2025)
IntroductionThe “simulation hypothesis” is a radical idea which posits that our reality is a computer simulation. We wish to assess how physically realistic this is, based on physical constraints from the link between information and energy, and based on known astrophysical constraints of the Universe.MethodsWe investigate three cases: the simulation of the entire visible Universe, the simulation of Earth only, or a low-resolution simulation of Earth compatible with high-energy neutrino observations.ResultsIn all cases, the amounts of energy or power required by any version of the simulation hypothesis are entirely incompatible with physics or (literally) astronomically large, even in the lowest resolution case. Only universes with very different physical properties can produce some version of this Universe as a simulation.DiscussionIt is simply impossible for this Universe to be simulated by a universe sharing the same properties, regardless of technological advancements in the far future.